2013
DOI: 10.1007/s10608-013-9578-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Interpretation Bias Modification in Depressed Adolescents and Young Adults

Abstract: This study evaluated the efficacy of a four-session Cognitive Bias Modification-Interpretation program for 45 depressed adolescents and young adults (14–21 years old; 12 males, 33 females; Beck Depressive Inventory, Second Edition ≥ 14) randomized to an active intervention condition (repeated exposure to positive outcomes of depression-relevant ambiguous scenarios; n=23) or a control condition (n=22). Both conditions experienced reductions on a Test of Interpretation Bias at post-treatment, with no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 61 publications
7
54
1
1
Order By: Relevance
“…Specifically, training led to more positive and less negative interpretations for those who started out with relatively lower levels of interpretation bias, but not for those who started out with relatively higher levels of interpretation bias. This is contrary to some past research, which found CBM-I effects were enhanced for participants with higher levels of baseline bias (e.g., Micco et al, 2014; Salemink & Wiers, 2011). Perhaps the small dose of training in the current study is sufficient to help those with less extreme and less rigid biases, but more training is needed to help those with more intense initial biases.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, training led to more positive and less negative interpretations for those who started out with relatively lower levels of interpretation bias, but not for those who started out with relatively higher levels of interpretation bias. This is contrary to some past research, which found CBM-I effects were enhanced for participants with higher levels of baseline bias (e.g., Micco et al, 2014; Salemink & Wiers, 2011). Perhaps the small dose of training in the current study is sufficient to help those with less extreme and less rigid biases, but more training is needed to help those with more intense initial biases.…”
Section: Discussioncontrasting
confidence: 99%
“…However, both studies applied the training to relatively unexplored samples. For example, the study by Micco et al (2014) trained depressed adolescents and young adults, whereas Beadel et al (2014) trained individuals scoring high in obsessive-compulsive beliefs. Moreover, the latter study also addressed a methodological aspect and investigated the trajectories of change processes over the course of the CBM-I training, including the assessment of cognitive and physiological responses.…”
mentioning
confidence: 99%
“…However, undergoing only one session of CBM-I did not proof to be sufficient to affect mood and stress reactivity in MDD [40], and repeated CBM-I does not seem to be effective in reducing depressive symptomatology in a subclinically depressed sample consisting of adolescents and young adults [27]. …”
Section: Interpretation Bias Modificationmentioning
confidence: 92%
“…Research indicates that identification with these situations is important for beneficial training effects to occur [26], as well as presence of a negative bias at baseline [27].…”
Section: Interpretation Bias Modificationmentioning
confidence: 99%